VD_FINDINFO Jug / 2015 / 303 vom 8. Mai 2015 - VD Tribunal cantonal (2015)
ADMISSION DE LA DEMANDE, INDEMNITÉEN GÉNÉRAL, CONTRAVENTION, ACQUITTEMENT | 398 al. 4 CPP (CH), 406 al. 1 let. d CPP (CH), 429 al. 1 let. a CPP (CH), 14 al. 3 LVCPP